(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Requiescat in loco sacro: first reflections on the use of Catholic churches as columbaria between the needs of the Church and the complexity of regional regulations ABSTRACT: In recent decades, the Catholic Church has changed its position on the cremation of the faithful departed, moving from a decidedly anti- cremation stance to a more open-minded one. For various reasons, including the lack of space in cemeteries and the significantly lower costs compared to burial, the use of cremation has increased exponentially. Thus, the hostile connotation of this practice with respect to the Church’s doctrine on the resurrection of bodies has been lost. Therefore, in some countries, such as Germany, the conversion of redundant churches into columbaria, i.e. places where the ashes of the faithful can be kept, has become widespread, while maintaining the sacred character of the place. This contribution, starting from the creation of a special commission on the matter by the Archdiocese of Bologna, which resulted in the two questions answered by the Prefect of the Dicastery for the Doctrine of the Faith on 9 December 2023, intends to present the problematic profiles of this solution in the Italian context, in the light of the complexity and plurality of regional regulations about mortuary police. SOMMARIO: 1. I quesiti del card. Zuppi e il lavoro della commissione Cinerarium - 2. L’evoluzione della posizione della Chiesa cattolica sulla cremazione - 3. La legislazione italiana sulla cremazione tra disciplina statale e normative regionali – 4. Prospettive per l’utilizzo delle chiese cattoliche come colombari